The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: cosmological implications of the Fourier space wedges of the final sample - Grieb, J. N.; Sanchez, A. G.; Salazar-Albornoz, S.; Scoccimarro, R.; Crocce, M.; Dalla Vecchia, C.; Montesano, F.; Gil-Marin, H.; Ross, A. J.; Beutler, F.; Rodriguez-Torres, S.; Chuang, C. H.; et al. (My University, 2017)
We extract cosmological information from the anisotropic power-spectrummeasurements from the recently completed Baryon Oscillation Spectroscopic Survey (BOSS), extending the concept of clustering wedges to Fourier space. Making use of new fast-Fourier-transform-based estimators, we measure the power-spectrum clustering wedges of the BOSS sample by filtering out the information of Legendre multipoles l > 4. Our modelling of these measurements is based on novel approaches to describe non-linear evolution, bias and redshift-space distortions, which we test using synthetic catalogues based on large-volume N-body simulations. We are able to include smaller scales than in previous analyses, resulting in tighter cosmological constraints. Using three overlapping redshift bins, we measure the angular-diameter distance, the Hubble parameter and the cosmic growth rate, and explore the cosmological implications of our full-shape clustering measurements in combination with cosmic microwave background and Type Ia supernova data. Assuming a Lambda cold dark matter (Lambda CDM) cosmology, we constrain the matter density to Omega M = 0.311(-0.010)(+ 0.009) and the Hubble parameter to H-0 = 67.6(-0.6)(+0.7) km s(-1) Mpc(-1), at a confidence level of 68 per cent. We also allow for nonstandard dark energy models and modifications of the growth rate, finding good agreement with the Lambda CDM paradigm. For example, we constrain the equation-of-state parameter to omega =-1.019(-0.039)(+0.048) . This paper is part of a set that analyses the final galaxy-clustering data set from BOSS. The measurements and likelihoods presented here are combined with others in Alam et al. to produce the final cosmological constraints from BOSS.
Citation: Grieb, J. N., Sanchez, A. G., Salazar-Albornoz, S., Scoccimarro, R., Crocce, M., Dalla Vecchia, C., . . . Zhao, G. B. (2017). The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: cosmological implications of the Fourier space wedges of the final sample. Monthly Notices of the Royal Astronomical Society, 467(2), 2085-2112. doi:10.1093/mnras/stw3384
Keywords: Cosmological Parameters; Cosmology: Observations; Dark Energy; Large; #NAME?; Digital Sky Survey